Cancer stem cells as therapeutic targets of pancreatic cancer. (11th December 2019) - Razi, Ebrahim; Radak, Mehran; Mahjoubin-Tehran, Maryam; Talebi, Samaneh; Shafiee, Alimohammad; Hajighadimi, Sarah; Moradizarmehri, Sanaz; Sharifi, Hossein; Mousavi, Nousin; Sarvizadeh, Mostafa; Nejati, Majid; Taghizadeh, Mohsen; et al.
Abstract: The discovery of stem cells and their potential abilities in self‐renewal and differentiation has opened a new horizon in medicine. Scientists have found a small population of stem cells in some types of cancers with the same functions as normal stem cells. There are two models for tumor progression: clonal (stochastic) and cancer stem cell (CSCs) models. According to the first model, all transformed cells in the tumor have carcinogenic potential and are able to proliferate and produce the same cells. The latter model, which has received more attention recently, considers the role of CSCs in drug resistance and tumor metastasis. Following the model, researchers have found that targeting CSCs may be a promising way in cancer therapy. This review describes CSC characteristics in general, while also focusing on CSC properties in the context of pancreatic cancer.